Juegos escénicos para fomentar la creatividad en la universidad contemporánea - reyes rivero, mirian; Martínez Batista, Maybel (Revista Eletrónica KULONGESA – TES. ISSN 2707-353X, 2020)
Creativity is one of the most important and useful capabilities of the human being. Being part of the theatrical stage games is one of the most effective ways to achieve in students a good interpretation of the character they want to reach. With this work we propose scenic games from the theater workshop to encourage creativity. With the application of these students were motivated to create dramatizations and improvisations in the workshop. The results can be seen in the festivals and events they have inside and outside the university community.